Salary scale and the diversity of wage systems - Jayady, Arman; Subekti, Priyo; Smyshlyaev, Alexey V.; Protasova, Olga N.; Artha, Ruly (Linguistics and Culture Review, 2021)
In any society or group, the behavior and manner of acting that are highly rated can be estimated based on the level of appreciation given by the group to that level of behavior. This reward system will be studied to show the kinds of behavior group members are expected to get by the group and the kinds of behavior that - through the reward system - will be strengthened and perpetuated in the group. The study of the wage and incentive systems of Japanese factories revealed very well the differences between Western industry and modern Japanese industry. The study also showed both the types and magnitude of the differences that underlie attitudes and behaviors that distinguish modern industry in Japan from that in the United States. In the following discussion, the wage system in one factory will be examined in detail to illustrate the particular central trend that appears in all studied factories. Since the monetary wage system for work performed is only a part of the entire wage system, it will also examine the general pattern of non-monetary benefits, welfare efforts, incentive programs for workers, using specific plans and costs of a particular factory.